2017
DOI: 10.1371/journal.pone.0181039
|View full text |Cite
|
Sign up to set email alerts
|

An update on psoriasis and metabolic syndrome: A meta-analysis of observational studies

Abstract: The relationship between psoriasis and metabolic syndrome is not well understood. Though multiple epidemiologic studies have suggested a link between psoriasis and metabolic syndrome, there is a lack of a comprehensive meta-analysis synthesizing the results of all available observational studies to date. In this meta-analysis, we examined global data on the relationship between psoriasis and odds of metabolic syndrome by searching for studies published between 1946–2016. Specifically, we analyzed the results f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
93
2
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 68 publications
1
93
2
8
Order By: Relevance
“…TNF‐α is involved in the pathogenesis of insulin resistance by reducing the expression of glucose transporter type 4 mainly located in adipocytes, skeletal and cardiac muscles . Previous studies have demonstrated a higher incidence of metabolic syndrome in chronic inflammatory disorders, such as psoriasis and rheumatoid arthritis . Compared with psoriatic patients without metabolic syndrome, higher levels of IL‐17, IL‐23 and TNF‐α were observed in psoriatic patients with metabolic syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…TNF‐α is involved in the pathogenesis of insulin resistance by reducing the expression of glucose transporter type 4 mainly located in adipocytes, skeletal and cardiac muscles . Previous studies have demonstrated a higher incidence of metabolic syndrome in chronic inflammatory disorders, such as psoriasis and rheumatoid arthritis . Compared with psoriatic patients without metabolic syndrome, higher levels of IL‐17, IL‐23 and TNF‐α were observed in psoriatic patients with metabolic syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…All these factors induce endothelial dysfunction, which promotes leucocyte adhesion and favours a prothrombotic state . Regarding the metabolic syndrome (MS), a systemic inflammatory and prothrombotic disease, a recent meta‐analysis confirmed a strong association between this syndrome and psoriasis (OR 2.14; 95% CI 1.84–2.48) . All this would lead to a higher cardiovascular disease mortality in psoriasis (OR 1.37: 95% CI 1.17–1.60), myocardial infarction (OR 3.04, 95% CI, 0.65–14.35) and stroke (OR 1.59, 95% CI, 1.34–1.89) .…”
Section: Introductionmentioning
confidence: 99%
“…Patients with psoriasis, and especially severe psoriasis, seem to have unfavourable levels of cardiovascular disease risk factors such as hypertension, dyslipidaemia and obesity, as well as established cardiovascular disease, metabolic syndrome and diabetes . Studies on the association between psoriasis and cardiovascular diseases and metabolic syndrome have been conducted since the 1970s, and a recent meta‐analysis of 35 studies found a pooled odds ratio for metabolic syndrome in psoriasis patients of 2.14 (95% CI 1.84, 2.48) . Systemic inflammation in psoriasis is put forward as an explanation of these associations, and aggressive screening of patients with psoriasis has been suggested .…”
Section: Introductionmentioning
confidence: 99%